Gametogenesis in Chlamydomonas eugametos: I. Light Requirements - Lorch, Steven K. (1973)
Male and female mating types of Chlamydomonas eugametos Moewus show an absolute light requirement for gametogenesis. Increasing light intensity from 0.3 to 1.2 mw cm(−2) during nitrogen starvation (a precondition for gametogenesis) caused an increase in gametogenesis throughout a 28-hour period. Gametogenesis was measured by determining the percentage of paired cells after a 1-hour mixing period. Light requirements for the male and female differed. There was a 9-hour lag period in gametogenesis in the male, but no lag in the female. Gametogenesis was reduced 50% in the female and 90% in the male when 6.0 μm 3-(3,4-dichlorophenyl)-1, 1-dimethyl-urea was in the N-starvation medium. Sodium acetate, 1.8 mm, in the N-starvation medium increased gametogenesis in both mating types and eliminated the 9-hour lag in the male for cells irradiated for 3, 6, 9, 12, 15, 18, or 23 hours during the last part of a 23-hour N-starvation period. Sodium acetate concentrations higher than 1.8 mm inhibited the mating process. 3-(3,4-Dichlorophenyl)-1, 1-dimethylurea inhibition of gametogenesis was decreased in the male but increased in the female, when sodium acetate was added to the N-starvation medium. These results indicate a nonphotosynthetic as well as a photosynthetic role for light in the gametogenesis of both mating types. Also, the male will not undergo gametogenesis unless a required amount of energy is provided either in the medium or through photosynthesis.